ANALISIS PERCIEVED USED VALUE DAN PRICE VALUE KONSUMEN TERHADAP SEPEDA MOTOR DI KOTA SURAKARTA - Wibowo, Muladi (Buletin Studi Ekonomi; VOL.19.NO.1.FEBRUARI 2014.(PP 1-117), 2016)
Analysis used perceived value and consumer price value of motor vehicles in Surakarta. The objectives of this research are to know the behavior of consumers in Surakarta base on  valuation percieved used value and percieved price value to the product of Honda, Yamaha and Suzuki. This research took place in the city of Surakarta.The data was collected using a questionnaire. The research sample are 204 respondents using cluster random sampling method  in 51 villages. Data analysis methods used in the research were validity test, reliability test, percieved price value analysis, percieved used analysis. Percieved value analysis result shows that the price value factor and purchase price vehicle become the most important factor in the global dimension as the main price.Used percieved value analysis result shows that the aspect of durability (endurance) performance and service reliabilities as an  important global dimension to the company.In general, performance based on PUV and PPV prominent factor of Honda, Suzuki and Yamaha vehicles are the aspects of performance, durabilty, aspects of the purchase price and maintenance costs.   Keywords:price value, used value, Customer Satisfaction
Keywords: price value, used value, Customer Satisfaction